Conceptualizing Russia-Turkey Strategic Political Competition - K.H. Abudalbouh, Walid; Abu Anzeh, Mohammed (Dirasat: Human and Social Sciences, 2022)
The Russia-Turkey relationship has risen to become one of the key dynamics defining contemporary geopolitics in the MENA region. The often febrile nature of this bilateral relationship, manifesting in the world’s most febrile region, makes it a worthy and important topic of analysis. Hence, the research rises the question of what are the key driving trends and dynamics define the bilateral relations within such complicated political strategic competition? The hypothesis that there are three key driving trends and dynamics define the bilateral: firstly, the ability for both sides to overlook their competing interests in order to pursue strategically advantageous cooperation; secondly, the shared aim of both nations to use each other to increase their respective autonomy from the West; and thirdly, the economic interdependency that incentivises both sides to maintain cooperation, even if the asymmetry of this interdependence, favouring Russia, has the potential to be used as leverage. Following an examination of these historical trends, the analysis will then expand on these dynamics and show how they’re manifesting in the current bilateral relationship through the extrapolation of the two key case studies of current Russian-Turkish engagement: the Syrian and Libyan conflicts